Cumulative meta-analysis and trial sequential analysis of correlation between hOGG1 Ser326Cys polymorphism and the risk of head and neck squamous cell carcinoma - Yan, Yan; Deng, Ai-Ping; Chen, Wen; Ming, Yu-Hua; Zeng, Xian-Tao; Leng, Wei-Dong (Oncotarget, 2018)
The human 8-oxoguanine glycosylase 1 ( ) Ser326Cys polymorphism has been involved in the risk of head and neck squamous cell carcinoma (HNSCC), but the results of published studies on this topic still inconsistent. Finally 11 qualified publications with 13 independent case-control studies were yielded. Overall, we observed significant differences in CysCys vs. SerSer [odds ratio (OR) = 1.55, 95% confidence interval (95% CI) = 1.01-2.38] and CysCys vs. SerCys+SerSer (OR = 1.42, 95% CI = 1.005-1.99) genetic models. Sensitivity analyses showed the results were not robust, cumulative meta-analyses and trial sequential analysis indicated the results didn't not need more studies to identification. Subgroup analyses showed there was a significant association in Caucasian, laryngeal squamous cell carcinoma, studies agreement with Hardy-Weinberg equilibrium, and alcohol drinkers subgroups under the corresponding contrasts. In addition, the results of Egger's test were contradictory. All eligible studies were searched from the online databases including PubMed, Web of Science, China Knowledge Resource Integrated Database, and Wanfang databases up to February 10, 2017. After study selection and data extraction, the meta-analysis was performed using STATA 12.0 software and TSA software version 0.9 Beta. Our meta-analysis results indicated that Ser326Cys polymorphism may be associated with increased risk of HNSCC, especially in Caucasians, alcohol drinkers and the patients with laryngeal squamous cell carcinoma.